PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA PEMBUDIDAYA LELE DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Faakhira Nadia Syakina; Yaktiworo Indriani; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to analyze the contribution of catfish cultivation enlargement to household income and the welfare of catfish cultivators household.  The research data was collected in Sub-District of Natar of South Lampung regency in December 2017 - January 2018. Respondents in this research were 30 cultivators of catfish enlargement, chosen on purpose for they have been actively running their business and 4 expert people in catfish cultivation.  Primary data was obtained by interviewing the respondents, while secondary data was obtained from several related institutions. Collected household income was included cultivation income of catfish, off-farm income, and non-farm income.  The level of household welfare was analyzed by three criterias namely Sajogyo, Badan Pusat Statistik (BPS) and Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN).  The  result showed that the average income of catfish cultivators business contributed 44,27 percent of the total household income of Rp52.340.376,00 per year. The household welfare level based on Sajogyo showed that 20 percent of households were in the almost-poor category, 50 percent in moderate, and 30 percent in decent living class. Based on BPS and BKKBN category showed that 20 percent of households were in the less prosperous and 80 percent were prosperous.Key words: catfish, income, welfare